Safeguarding Social Security: The challenge of financing the baby boom's retirement - Walter M. Cadette (Levy Economics Institute of Bard College, 1997)
The falling ratio of workers to retirees in the United States has raised concerns about Social Security's ability to continue to provide a base level of support for all retired workers and to remain in balance with all of government's other fiscal obligations. Of alternative plans that have been proposed to safeguard the system, Walter Cadette argues against radical revamping through privatization and suggests instead minor modifications in the existing tax and benefits structure.
Keywords: 330